Influence of osmolytes on the stability of thylakoid‐based dye‐sensitized solar cells. (9th September 2019) - Voloshin, Roman A.; Brady, Nathan G.; Zharmukhamedov, Sergey K.; Feyziyev, Yashar M.; Huseynova, Irada M.; Najafpour, Mohammad Mahdi; Shen, Jian‐Ren; Veziroglu, T. Nejat; Bruce, Barry D.; Allakhverdiev, Suleyman I.
Summary: In recent years, there has been considerable interest in incorporating naturally occurring components of the photosynthetic apparatus into man‐made solar cells, because of the high quantum efficiency of photosynthetic reaction centers. One hurdle to overcome regarding the use of native membranes in these devices is their limited lifespans. In this study, we used stabilizers to increase the long‐term viability of biomolecules in vitro, thereby alleviating this challenge. In this regard, it is known that osmolytes, such as glycine betaine (GB) and sucrose, preserve photosynthetic activity in isolated photosystems. Upon investigation of the thermal protection properties of GB and sucrose in thylakoid‐based dye‐sensitized solar cells, we report that the addition of GB and sucrose to the thylakoid photosensitizer maintains nonzero photocurrent in the thylakoid‐based solar cell upon heating to 50°C. At 50°C, the GB‐containing cell displayed about a fourfold increase in photocurrent than the control cell, in which the photocurrent was decreased to nearly zero. The addition of 0.5M and 1M sucrose has respectively caused nearly 40% and 70% increases in photoinduced electron transfer activity over the control at 35°С. Similarly, though to a lesser extent, 1M GB caused an approximate 40% increase in electron transfer activity as well. Moving forward, this approach will be extended to alternative membrane protein isolation strategies, allowing for an accurate comparison with traditional detergent‐isolated complexes, with the ultimate goal of developing a cost‐effective and sustainable solar cell. Abstract : Cosolutes that stabilize photosystems can increase the efficiency of thylakoid‐based solar cell. Cosolutes at high concentration hinder attachment of the thylakoids to the TiO2 . Sucrose and GB increase the photocurrent of thylakoid‐based solar cells at elevated temperature.